Peran mediasi literasi keuangan dalam keputusan investasi bagi Generasi Z: Pengujian bias-bias perilaku - Aulia, Syafitri; Giriati, Giriati; Mustika, Uray Ndaru; Mustaruddin, Mustaruddin (Nur Science Institute, 2024)
This study analyzes behavioral factors, namely overconfidence, representativeness, and availability in Generation Z in making investment decisions, with financial literacy as a mediating variable. The research used a quantitative approach with a purposive sampling method. The data used are primary data with cross-sectional data types. Respondent data collection used a questionnaire distributed online to 250 respondents. The data analysis method used path analysis and the Sobel test. The results showed that overconfidence and representativeness positively and significantly affected financial literacy. The variables overconfidence, availability, and financial literacy positively and significantly affected investment decisions. This result is inversely proportional to the availability test on financial literacy and representativeness on investment decisions, indicating no effect. Financial literacy as a connecting variable can mediate the three behavioral biases on investment decisions.